Relationship between Defense Mechanism and Adjustment among Undergraduate Students - Kader, Noora Abdul; Moeed, Abdul (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Using defense mechanism is a natural process unless it is used in a proper and healthy way. When used in an ineffective way to cope with adjustment problems of the individual’s life it may create serious issues. The study was quantitative and descriptive in nature. Survey method was used for the study and proportionate stratified simple random sampling technique was used for selecting the sample. The study was conducted on a sample of 100 under graduate students of Aligarh Muslim University, giving due representation to gender and stream of study. Two inventories, namely, defense mechanism inventory and adjustment inventory were used for collecting the data. Correlation and mean difference analysis were the statistical techniques used for the analysis. The result of the study revealed that there is a significant relationship between defense mechanism and adjustment among undergraduate students.